Identification of long noncoding RNAs involved in plumule-vernalization of Chinese cabbage - Dai, Yun; Li, Guoliang; Gao, Xinyu; Wang, Shaoxing; Li, Ze; Song, Chao; Zhang, Shifan; Li, Fei; Fang, Zhiyuan; Sun, Rifei; Zhang, Hui; Zhang, Shujiang (Frontiers in Plant Science, 2023)
Vernalization is a phenomenon in which plants must undergo a period of continuous low temperatures to change from the vegetative growth stage to the reproductive growth stage. Chinese cabbage is a heading vegetable, and flowering time is an essential developmental trait. Premature vernalization leads to premature bolting, which causes a loss of product value and yield. While research into vernalization has provided a wealth of information, a complete understanding of the molecular mechanism for controlling vernalization requirements has not yet been elucidated. In this study, using high-throughput RNA sequencing, we analyzed the plumule-vernalization response of mRNA and long noncoding RNA in the bolting-resistant Chinese cabbage double haploid (DH) line ‘Ju Hongxin’ (JHX). A total of 3382 lncRNAs were identified, of which 1553 differentially expressed (DE) lncRNAs were characterized as plumule-vernalization responses. The ceRNA network revealed that 280 ceRNA pairs participated in the plumule-vernalization reaction of Chinese cabbage. Through identifying DE lncRNAs in Chinese cabbage and analyzing anti-, cis-, and trans-functional analysis, some candidate lncRNAs related to vernalization promoting flowering of Chinese cabbage and their regulated mRNA genes were found. Moreover, the expression of several critical lncRNAs and their targets was verified using qRT-PCR. Furthermore, we identified the candidate plumule-vernalization-related long noncoding RNAs that regulate BrFLCs in Chinese cabbage, which was interesting and different from previous studies and was a new discovery. Our findings expand the knowledge of lncRNAs in the vernalization of Chinese cabbage, and the identified lncRNAs provide rich resources for future comparative and functional studies.